Safe and sound banking practices in Nigeria : selected essays - Ebhodaghe, John U.; Umoh, Peter Nyong (Lagos : Page Publishers Services, 1997)
Bank deposit insurance schemes developed out of the need to protect depositors, especially by uniformed, from the risk of loss; and to also protect the banking system from instability occasioned by runs and loss of confidence.The second section provides an overview of banks' contributions to economic development.
"An NDIC book"--Added t.p.
Includes bibliographical references.
aia 6/9/16
Loans
Keywords: Banks and banking; Banks and Banking- Nigeria; Banking practices